State responsibility for 'modern slavery' in human rights law : a right not to be trafficked - Jovanović, Marija, 1982- (Oxford : Oxford University Press, 2023)
Do humans have a right not to be trafficked? This book examines the legal nature of human trafficking and its relationship with human rights law. Drawing on the jurisprudence of the European Court of Human Rights, it shows that human trafficking is indeed a human rights violation requiring legislative and institutional responses from states.
This edition also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Human rights; Human trafficking (International law); Government liability (International law); European Court of Human Rights; Slavery -- Law and legislation; Law; International law